Aging and multiple sclerosis. (May 2016) - Sanai, Shaik Ahmed; Saini, Vasu; Benedict, Ralph HB; Zivadinov, Robert; Teter, Barbara E; Ramanathan, Murali; Weinstock-Guttman, Bianca
The life expectancy and average age of persons with multiple sclerosis (MS) have increased significantly during the last two decades. The introduction of disease-modifying therapies and a better delineation and understanding of the superimposed comorbidities often diagnosed in MS patients are probably the most important factors accountable for the increase in aging MS population worldwide. Healthcare teams must therefore address the problems arising due to advancing age superimposed on this chronic neurologic disease. In this review, we focus on the physiology of aging, its effects on MS disease course, and the pathological and immunological changes associated with aging and disease progression. Additionally, we discuss the common comorbidities that occur in aging persons with MS that may arise either as a result of the aging process or from relentless chronic MS disease progression as well as the challenges on differentiating the two processes for a more appropriate therapeutic approach.